Effect of Increased Flexor Hallucis Longus Muscle Activity on Ground Reaction Force during Landing - Kosuke Oku; Daisuke Kimura; Tomotaka Ito; Akiyoshi Matsugi; Tatsuya Sugioka; Yusuke Kobayashi; Hayato Satake; Tsukasa Kumai (Life, 2021)
Repeated high-impact ground forces can lead to injury and decreased performance. While increasing flexor hallucis longus (FHL) muscle activity is known to increase stiffness and elasticity, it is unknown if this also decreases ground reaction forces by shock absorption during landing. This study aimed to determine whether increasing FHL muscle activity affects ground reaction force during landing in healthy subjects. Eight subjects performed single-leg steps onto a force platform for five trials, with and without flexion of the metatarsophalangeal (MTP) joint at the moment of landing. Integrated surface electromyography (sEMG) of the FHL and medial gastrocnemius (MG) and ground reaction forces (GRFs) were measured. sEMG and GRF during the 50 ms before and 100 ms following initial ground contact were analyzed and compared. Flexion of the MTP joint condition significantly decreased the vertical and mediolateral force peaks of GRF, and FHL muscle activity increased. Flexion of the MTP joint at the moment of landing reduces GRF in healthy subjects through force dissipation in the foot, by increased FHL muscle activity. The results suggest that this may contribute to injury prevention by reducing the impact force through flexing the MTP joint at the moment of landing.